GENDERED PATHWAYS TO POLITICAL EMPOWERMENT: THE ROLE OF SPECIAL SEATS IN TANZANIA’S PARLIAMENT, 2020-2025 - Valentine flavian Ruhangisa; Chusnul Mar'iyah (Kafa`ah: Journal of Gender Studies, 2026)
Despite constitutional gender quotas and a long-standing special seats system in Tanzania, questions persist regarding whether these mechanisms translate into genuine political empowerment for women or merely tokenistic inclusion. This study examines the impact of special seats on women's political empowerment in Tanzania's Parliament during the 2020–2025 term. Employing a qualitative instrumental case study design, data were collected through in-depth interviews with 15 women parliamentarians (eight special seat holders and seven constituency-based MPs), two focus group discussions with parliamentary staff and gender activists, and document analysis of Hansard transcripts, committee reports, and party documents. The findings reveal three interrelated themes. First, the Paradox of Presence shows that while special seats have significantly increased numerical representation (women hold 36.7% of seats), special seat MPs (SSMPs) face legitimacy deficits compared to constituency-based MPs (CEMPs), though some CEMPs acknowledge SSMPs' complementary technical expertise. Second, Navigating the Institutional Labyrinth demonstrates that SSMPs are disproportionately assigned to 'soft' committees (social services, health, gender) and excluded from 'hard' committees (finance, defence, infrastructure), while party dependence severely constrains their autonomy. Third, The Voice for Gender reveals that SSMPs are the most vocal advocates for gender-sensitive legislation, playing decisive roles in debates on the Law of Marriage Act, gender-based violence, and maternal health. Using a tripartite conceptual framework distinguishing agency (individual capacity), structure (institutional opportunities/constraints), and achievement (policy outcomes), the study finds that special seats effectively enable structural access but unevenly produce agency and achievement. Comparative insights from India, Nepal, Rwanda, and Nordic countries indicate that Tanzania's intra-gender hierarchy is distinctive yet shows generalisable patterns of party control and committee ghettoisation. The study concludes that special seats are necessary but insufficient for transformative empowerment, requiring complementary reforms in party nominations, committee assignments, cross-party caucuses, and capacity-building.